Military Court Authority to Adjudicate Serious Human Rights Violations Committed by TNI Personnel - Ramadhan, Azis Akbar; Firdausi, Ulya Shafa; Putri, Cerninta Khisan Kusuma Pratama (NAJAHA, 2024)
This study examines the Military Court's legal process and authority in trying to resolve human rights violations committed by TNI personnel. Normative legal research is used with a legislative approach and a conceptual approach, which is then analyzed against laws and regulations related to the problem to determine which court has the authority to try the case. The analysis results show that the Military Court's rule is to try criminal acts committed by a soldier, who according to the law is considered equal to a soldier, and members of a group or position or agency are considered soldiers according to the law. Military courts in the military justice system, even though they are under the jurisdiction of a special court, namely the human rights court in the general justice system.